Preparation and in vitro evaluation of polyurethane composite scaffolds based on glycerol esterified castor oil and hydroxyapatite. (April 2014) - Du, J. J.; Zuo, Y.; Zou, Q.; Sun, B.; Zhou, M. B.; Li, L. M.; Man, Y.; Li, Y. B.
Abstract : Sponge-like polyurethane (PU) and composite have recently attracted attention in biomedical field as scaffolds for bone repair or tissue engineering research. In this study, castor oil was transesterified with glycerol to increase its functional hydroxyl groups and improve the mechanical properties of the resulting composite scaffolds. The glyceride of castor oil (GCO) was used to copolymerise with isophorone diisocyanate to generate PU, meanwhile blending with hydroxyapatite (HA) powder to prepare porous HA/PU composite scaffolds. The HA/glyceride based PU (GCPU) scaffolds were compared with pristine castor oil (PCO) based PU scaffolds (PCPU) by investigating the physicochemical properties and cytocompatibility using Fourier transform infrared, X-ray diffraction, SEM, mechanical testing and methylthiazolyldiphenyl-tetrazolium bromide assay. The results showed that the number of hydroxyl groups of GCO was nearly twice as high as that of PCO, which enhanced efficiently the crosslinking density of PU matrix. The compressive strength of HA/GCPU scaffold with 40 wt-%HA was ∼4·6 MPa, much higher than that (0·058 MPa) of HA/PCPU scaffolds. The in vitro biological results demonstrated that both GCPU and HA/GCPU scaffolds exhibited desirable cytocompatibility. The novel synthetic route is highly effective for the preparation of HA/GCPU porous scaffolds, which have good prospect in the repair of bone defects or for bone tissue engineering.